What does healthy eating mean? Australian teachers' perceptions of healthy eating in secondary school curricula. Issue 4 (3rd June 2019) - Boddy, Gail; Booth, Alison; Worsley, Anthony
Abstract : Purpose: Teachers disseminate food knowledge and skills in secondary school curricula that provide essential skills for a healthy life. The purpose of this paper is to explore Australian secondary school teachers' views of healthy eating and their sources of information in planning their food, nutrition and health curriculum. Design/methodology/approach: Secondary school teachers' perceptions were explored through semi-structured, in-depth interviews that were de-identified and transcribed verbatim. Codes were ascribed to sections of the transcripts and throughout the process of inductive thematic analysis. The teachers' responses were grouped into five main themes: approaches to teaching healthy eating, sources of food and nutrition information, curriculum planning, teaching goals and teacher career influences. Findings: The teachers were clear about the aims and importance of teaching healthy eating in an experiential curriculum. They reported that teaching healthy eating assists the health and well--being of adolescents and their families. The effectiveness of current teaching in Australian secondary schools may be compromised by the positioning of food, nutrition and health topics in two separate curriculum areas: technologies and health and physical education, and competing school priorities and resources that limit the students' exposures to food curricula. The teachers sourced food information from online websites, popular culture and social media. Their knowledge and views of healthy eating appeared to be associated with their interests, life experiences, education and employment histories. Practical implications: These findings can assist with health promotion and education policy development. They can assist the design of healthy eating curriculum approaches for secondary schools and professional development courses for teachers, which will foster healthy food habits for adolescents, and their families in the future. Originality/value: Secondary school teacher perceptions of the place of healthy eating in food, and nutrition curricula have been under examined.